Juridical Review of Alternative Business Dispute Resolution as a Form of Consumer Rights Protection - Hidayat Sumarna, Muhammad; Djunaedi, O.; Rattanapun, Supot (Journal Evidence Of Law, 2024)
The settlement of business disputes between consumers and business actors is an increasingly crucial issue along with the increasing complexity of transactions in the digital era and global economy. The purpose of this research is to analyze the role of the Consumer Dispute Resolution Agency (BPSK) in supporting alternative business dispute resolution as an effort to protect consumer rights in Indonesia and analyze the effectiveness of alternative business dispute resolution in protecting consumer rights in Indonesia. The method used in this research is normative juridical research. The results showed that BPSK plays an important role in providing more effective alternative dispute resolution for Indonesian consumers through mediation, conciliation, and arbitration mechanisms that are friendly, fast, and affordable. Through this approach, BPSK supports the protection of consumer rights and encourages fair and responsible business practices among business actors. The effectiveness of alternative business dispute resolution also creates flexible and efficient solutions, addressing consumer justice needs in a cheaper and faster way. Despite some challenges, ADR provides a favorable solution for consumers and businesses in resolving business disputes..